Point redemption matters: A response to Murthi et al (2011). Issue 4 (December 2016) - Leavell, J.
Abstract Murthiet al (2011) addressed a controversy about the benefits of loyalty programs within the credit-card industry. One of their findings was that rewards cardholders were less profitable than non-rewards cardholders. This paper will address two opportunities for further research based on their finding. One opportunity is the investigation of rewards and non-rewards credit-card customers in a context which allows for more associations with the firm than just credit cards. Another opportunity is the segmentation of rewards cardholders into those redeeming rewards and those who do not. The present paper investigates the profitability of credit-card customers in terms of the credit card itself (product profit) and in terms of all of a firm's products held by the customer (relationship profit). Rewards cardholders are segmented based on their level of redemption. This study finds that cardholders who do not redeem points dilute the profitability of cardholders who do redeem their points when both segments are viewed together. Cardholders who redeem points are found to be more profitable than non-rewards cardholders in terms of both product and relationship. This study also finds that higher levels of redemption correspond with higher profitability at both the product and relationship levels.